Utilization of Nyctanthes arbor-tristis L and Artocarpus heterophyllus Lam extracts as natural dyes for sheepskins leather with different mordants - Dona Rahmawati; Umi Reza Lestari; Emiliana Kasmudjiastuti (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2020)
Natural dye, as dyeing material, delivers beautiful and distinctive color, synthetic chemical free, easy to get, easy to degrade, and produces non-toxic liquid waste. Natural dyes require mordant to attach the dye molecules into the leather fibers. This study aimed to determine the effect of mordant in the leather dyeing process using natural dyes extracted from Artocarpus heterophyllus Lam wood and Nyctanthes arbor-tristis L. flowers. The treatment was using three kinds of mordant, i.e. alum, citric acid, and zinc sulfate, with pre-mordanting method, 3% by weight of the sheepskins crust leather tanned with chrome and syntan. The result of the dry rub fastness was excellent (score 5). The wet rub fastness of dyed leather with citric acid mordant was good (score 4 - 4/5), while for alum mordant was quite good (score 3/4). Artocarpus heterophyllus Lam wood extract produced better wet rub fastness compared to Nyctanthes arbor-tristis L. flowers extract. Citric acid mordant produced colors with the highest brightness level for both natural dyes extracts compared to alum and zinc sulfate. Artocarpus heterophyllus Lam wood extract produced a brighter color compared to Nyctanthes arbor-tristis L. flowers extract with the same mordant. The visual result of the dyeing process was brownish-yellow.